Latin historiography and poetry in the early empire : generic interactions - Miller, John F., 1950-; Woodman, A. J. 1945- (Mnemosyne, Supplements, 2010)
This book, a sequel to Clio and the Poets (Brill 2002), takes as its point of departure Quintilian's statement that 'historiography is very close to the poets': it examines not only how verse interfaces with historical texts but also how first-century AD Roman historians engage with issues and patterns of thought central to contemporary poetry and with specific poetic texts. Included are substantive discussions of a wide range of authors, notably Lucan, Seneca, Statius, Pliny, Juvenal, Silius Italicus, and Tacitus.